THE SUPERVISION OF VEHICLE OPERATION MOTORCYCLE RICKSHAWS (BENTOR) IN GORONTALO CITY - Thalib, Tety; Aneta, Yanti (Universitas Negeri Gorontalo, 2023)
This study aims to find out the performance of vehicle operation supervision, in this case motorized rickshaws as transportation in the province of Gorontalo. This study used a qualitative descriptive method with data collection techniques using observation and literature review through data from the Department of Transportation. The results of this study indicate that the supervision from the aspect of human resources or field officers is inadequate. The average education of field officers was still high school graduates and had not attended any trainings that supported organizational tasks, therefore there were no officers who were devoted to supervising bentor in operation. So that this has the effect of being less effective in supervising the operating areas. In order to optimize supervision, it is necessary to have sanctions so that people who break the law or commit fraud can find out their mistakes and not repeat them and be disciplined if they comply with the rules.